Four‐times‐daily Dosing of Rabeprazole with Sitafloxacin, High‐Dose Amoxicillin, or Both for Metronidazole‐Resistant Infection with Helicobacter pylori in Japan. Issue 1 (23rd May 2016) - Sugimoto, Mitsushige; Sahara, Shu; Ichikawa, Hitomi; Kagami, Takuma; Ban, Hiromitsu; Otsuka, Taketo; Andoh, Akira; Furuta, Takahisa
Abstract: Background: The bacterial resistance of Helicobacter pylori to antimicrobial agents such as clarithromycin and metronidazole has been increasing worldwide, leading to the failure of eradication treatment. Here, we present an eradication regimen consisting of four‐times‐daily dosing (q.i.d.) of rabeprazole with potent acid inhibition. Aim: To investigate the efficacy of eradication therapy with rabeprazole q.i.d. and amoxicillin or sitafloxacin in Japanese infected with a metronidazole‐resistant strain. Methods: We retrospectively investigated the efficacy of eradication regimens with rabeprazole q.i.d. for 7 days in 111 Japanese pooled patients infected with a metronidazole‐resistant strain of H. pylori at Hamamatsu University School of Medicine Hospital or the Shiga University of Medical Science Hospital: 1, with sitafloxacin 100 mg twice daily (b.i.d.) (n = 82); 2, with amoxicillin 500 mg q.i.d. (n = 15); and 3, with amoxicillin q.i.d. and sitafloxacin b.i.d.‐combined regimen (n = 14). Eradication status was assessed at 8 weeks via a 13 C‐urea breath test. Results: Eradication rate on intention‐to‐treat analysis was 93.7% (95% confidence interval: 87.4–97.4%, 104/111), irrespective of the high prevalence of strains resistant to clarithromycin (81.1%, 90/111) and levofloxacin (42.3%, 47/111). No significant differences in eradication rates were observed among the different treatment regimens ( p = .408), eradication history ( p = .096) and different CYP2C19 genotypes ( p = .789). On multivariate analysis, no significant risk factor for eradication failure by therapy with potent acid inhibition was seen. Conclusion: In Japanese patients infected with metronidazole‐resistant strains of H. pylori, eradication rates exceeding 90% can be achieved using appropriate dosing of antibiotic agents with strain susceptibility (amoxicillin q.i.d. and/or sitafloxacin b.i.d.) together with acid inhibition for a full 24 h and rabeprazole 10 mg q.i.d. These findings may be further evidence for dual therapy with rabeprazole q.i.d. and an antibiotic agent (amoxicillin q.i.d. or sitafloxacin b.i.d.) in Japanese patients with metronidazole‐resistant strains.